Pre-baked carbon anode with high conductivity and oxidation resistance and preparation method of pre-baked carbon anode
By using multiple particle sizes of calcined petroleum coke and conductive carbon materials in the prebaked carbon anode, and improving the density through the binder, the problem of insufficient conductivity and oxidation resistance of the traditional prebaked carbon anode is solved, achieving high The synchronous improvement of conductivity and oxidation resistance provides technical support for energy saving and consumption reduction for aluminum electrolysis.
Patent Information
- Application Number
- CN202411415749.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The conductive and oxidation resistance of traditional prebaked carbon anodes cannot meet the energy-saving needs of the aluminum electrolysis industry, and when graphite powder is added to improve conductivity, the bulk density and pressure resistance strength index will decrease, affecting the overall performance.
The combination of calcined petroleum coke of multiple particle sizes and conductive carbon materials is used to replace part of the calcined petroleum coke with conductive carbon materials, and the compactness of the dry material is improved through the binder, which promotes the insertion between the conductive carbon materials and the calcined petroleum coke particles. and mosaic, reduce the internal porosity of the dry material, thereby improving conductivity and oxidation resistance.
The conductive and oxidative resistance of the prebaked carbon anode is synchronously improved, the resistivity is reduced to 46μΩ·m, the volume density reaches 1.58g/cm3, and the air reactivity residual rate reaches 80%, supporting the energy saving and consumption reduction of aluminum electrolysis.
Smart Images

Figure CN119287452A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon anodes for aluminum electrolysis, and in particular to a prebaked carbon anode with high conductivity and oxidation resistance and a preparation method thereof. Background Art
[0002] Prebaked carbon anodes are the heart of the aluminum electrolysis cell. The quality of these carbon anodes directly impacts the process technology and economics of the aluminum electrolysis cell. As aluminum electrolysis technology develops toward large-scale, high-efficiency, and energy-saving and consumption-reducing processes, the quality of prebaked carbon anodes is becoming increasingly important to electrolytic production. Because the energy consumption of prebaked carbon anodes directly impacts production energy consumption, the electricity cost of prebaked carbon anodes typically accounts for 40% to 50% of total production costs. Therefore, improving the conductivity and anode density of prebaked carbon anodes can effectively reduce production costs, providing technical support for energy conservation and carbon reduction in aluminum electrolysis.
[0003] At present, the average resistivity of traditional prebaked carbon anode is 57μΩ·m, and the average volume density of traditional prebaked carbon anode is 1.57g / cm 3 The air reactivity residual rate of traditional prebaked carbon anodes is 70%. The performance parameters of these traditional prebaked carbon anodes still cannot effectively meet the energy-saving needs of the aluminum electrolysis industry. Therefore, it is necessary to further improve the conductivity, oxidation resistance and volume density of prebaked carbon anodes. Although graphite powder can be added during the production process of prebaked carbon anodes to improve their conductivity, existing studies have found that with the increase in the proportion of graphite powder added, the volume density and compressive strength indicators of the prebaked carbon anodes show a downward trend, which in turn affects the comprehensive performance indicators of the prebaked carbon anodes. Summary of the Invention
[0004] The present application provides a prebaked carbon anode with high electrical conductivity and oxidation resistance and a preparation method thereof to solve the following technical problem: how to simultaneously improve the electrical conductivity and oxidation resistance of the prebaked carbon anode.
[0005] In a first aspect, the present application provides a prebaked carbon anode having high conductivity and oxidation resistance, wherein the raw materials of the prebaked carbon anode include a dry material of multiple particle sizes and a binder, wherein the total weight m1 of the dry material of multiple particle sizes and the weight m2 of the binder satisfy the relationship: m1:m2=(82:18)~(88:12);
[0006] The raw materials of the dry material include calcined petroleum coke of various particle sizes and conductive carbon materials of various particle sizes, and the calcined petroleum coke and the conductive carbon materials satisfy the following relationship:
[0007] m3:m4=(80~95):(5~20), and m31:m41=m3:m4;
[0008] In the formula, m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m31 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size.
[0009] Optionally, the first particle size and the second particle size are respectively greater than 0 and less than or equal to 8 mm.
[0010] Optionally, the dry materials of multiple particle sizes include dry materials of a first particle size, dry materials of a second particle size, dry materials of a third particle size, and dry materials of a fourth particle size;
[0011] The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is ≥0.97g / cm 3 ;
[0012] The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.9g / cm 3 ;
[0013] The particle size D2 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.82g / cm 3 ;
[0014] The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.76g / cm 3 .
[0015] Optionally, the bulk density of the dry material is ≥1.32 g / cm 3 .
[0016] Optionally, the conductive carbon material includes at least one of the following:
[0017] Semi-graphite, artificial graphite, natural graphite and spent anode carbon blocks; and / or
[0018] The binder includes coal tar.
[0019] Optionally, the ash content of the conductive carbon material is less than 0.5%, the specific resistance of the conductive carbon material is less than or equal to 180 μΩ·m, and the Lc value of the conductive carbon material is less than or equal to
[0020] Optionally, the resistivity of the prebaked carbon anode is ≤46 μΩ·m, and the volume density of the prebaked carbon anode is ≥1.58 g / cm 3 , the air reactivity residual rate of the prebaked carbon anode is ≥80%.
[0021] In a second aspect, the present application provides a method for preparing the prebaked carbon anode according to the first aspect, the method comprising:
[0022] calcining petroleum coke to obtain calcined petroleum coke;
[0023] Mixing the conductive carbon material and the calcined petroleum coke to obtain a dry material;
[0024] Infiltrating the dry material with an adhesive to obtain a mixed material;
[0025] The mixed material is calcined to obtain a prebaked carbon anode.
[0026] Optionally, the wettability of the binder to the calcined petroleum coke in the mixture is greater than 1.36, the wettability of the binder to the conductive carbon material in the mixture is greater than 1.56, and the wettability of the binder to the mixture is greater than 1.39.
[0027] Optionally, the roasting includes a preheating section and a roasting section, the heating rate of the preheating section is ≤10°C / min, and the roasting temperature of the roasting section is ≥1060°C.
[0028] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0029] An embodiment of the present application provides a prebaked carbon anode with high conductivity and oxidation resistance, wherein the raw materials of the prebaked carbon anode include dry materials of multiple particle sizes and a binder, and the total weight m1 of the dry materials of multiple particle sizes and the weight m2 of the binder satisfy the relationship: m1:m2=(82:18)~(88:12); wherein the raw materials of the dry materials include calcined petroleum coke of multiple particle sizes and conductive carbon materials of multiple particle sizes, and the calcined petroleum coke and the conductive carbon material satisfy the following relationship: m3:m4=(80~95):(5~20), and m31:m41=m3:m4, wherein m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m31 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size. The raw materials of the dry material can include calcined petroleum coke of multiple particle sizes and conductive carbon materials of multiple particle sizes. Conductive carbon materials can be used to replace part of the calcined petroleum coke to improve the conductivity of the prebaked carbon anode. In addition, the calcined petroleum coke and the conductive carbon material can satisfy the following relationship: m3:m4=(80~95):(5~20), and m31:m41=m3:m4, and the first particle size is the same as the second particle size. , which can promote the synergistic intercalation of conductive materials and some particle sizes of calcined petroleum coke, and promote the mutual complementation and intercalation of materials of the same particle size in calcined petroleum coke and conductive carbon materials, so as to reduce the internal porosity of the dry material, thereby obtaining a dry material with high compactness. The dry material with high compactness can reduce the grain resistance and interface resistance, thereby improving the conductivity of the prebaked carbon anode; in addition, the total weight m1 of the dry material of multiple particle sizes and the weight m2 of the binder can satisfy the relationship: m1:m2=(82:18)~(88:12), and the density of the dry material can be further improved by the binder, and the dry material with higher density can improve the density of the prebaked carbon anode to isolate the entry of external oxygen, thereby improving the antioxidant performance of the prebaked carbon anode. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0032] Figure 1 A schematic diagram of a prebaked carbon anode with high conductivity and oxidation resistance provided in an embodiment of the present application;
[0033] Figure 2 A schematic flow chart of a method for preparing a prebaked carbon anode provided in an embodiment of the present application. DETAILED DESCRIPTION
[0034] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0035] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range; for example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited number (fractional or integer) within the indicated range.
[0036] In this document, the terms including "including" and "comprising" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "At least one" means one or more, "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in this application can be purchased on the market or prepared by existing methods.
[0037] Figure 1 A schematic diagram of a product of a prebaked carbon anode with high conductivity and oxidation resistance provided in an embodiment of the present application is shown as an example;
[0038] like Figure 1As shown, the embodiment of the present application provides a prebaked carbon anode with high conductivity and oxidation resistance, wherein the raw materials of the prebaked carbon anode include dry materials of multiple particle sizes and a binder, and the total weight m1 of the dry materials of multiple particle sizes and the weight m2 of the binder satisfy the relationship: m1:m2=(82:18)~(88:12);
[0039] The raw materials of the dry material include calcined petroleum coke of various particle sizes and conductive carbon materials of various particle sizes.
[0040] The calcined petroleum coke and the conductive carbon material satisfy the following relationship:
[0041] m3:m4=(80~95):(5~20), and m31:m41=m3:m4,
[0042] In the formula, m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m31 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size.
[0043] The total weight m1 of the dry materials of multiple particle sizes and the weight m2 of the binder satisfy the relationship: m1:m2=82:18, 83:17, 84:16, 85:15, 86:14, 87:13 or 88:12.
[0044] The calcined petroleum coke and the conductive carbon material satisfy the following relationship: m3:m4=80:20, 81:19, 82:18, 83:17, 84:16, 85:15, 86:14, 87:13, 88:12, 89:11, 90:10.
[0045] In some optional embodiments, the first particle size and the second particle size are respectively >0 and ≤8 mm;
[0046] In these embodiments, the first particle size and the second particle size can be respectively greater than 0 and less than or equal to 8 mm, which can promote a more uniform distribution between the particles of calcined petroleum coke and the conductive carbon material, thereby facilitating the mutual complementation and interlocking between materials of the same particle size in the calcined petroleum coke and the conductive carbon material, thereby reducing the internal porosity of the dry material, thereby obtaining a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode.
[0047] In some optional embodiments, the dry material of multiple particle sizes includes a first particle size dry material, a second particle size dry material, a third particle size dry material and a fourth particle size dry material;
[0048] The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is ≥0.97g / cm 3 ;
[0049] The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.9g / cm 3 ;
[0050] The particle size D3 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.82g / cm 3 ;
[0051] The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.76g / cm 3 ;
[0052] In these embodiments, the dry material may include a first-size dry material, and the particle size D1 of the first-size dry material may satisfy: 0 < D1 ≤ 0.074 mm, and the bulk density of the first-size dry material may be ≥ 0.97 g / cm 3 , which can make the finest particles in the dry material have a larger bulk density, so that the bulk density of the final dry material is ≥1.32g / cm 3 , thereby effectively reducing the internal porosity of the dry material to obtain a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode; in addition, the dry material may include a second particle size dry material, and the particle size D2 of the second particle size dry material satisfies: 0mm<D2≤1mm, and the bulk density of the second particle size dry material may be ≥0.9g / cm 3 , which can make the finer particles in the dry material have a larger bulk density, so that the final bulk density of the dry material is ≥1.32g / cm 3 , thereby effectively reducing the internal porosity of the dry material to obtain a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode; in addition, the dry material may include a third particle size dry material, and the particle size D3 of the third particle size dry material may satisfy: 1mm<D3≤4mm, and the bulk density of the third particle size dry material may be ≥0.82g / cm 3 , which can make the particles of normal size in the dry material have a larger bulk density, so that the bulk density of the final dry material is ≥1.32g / cm 3 , thereby effectively reducing the internal porosity of the dry material to obtain a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode; in addition, the dry material may include a fourth particle size dry material, and the particle size D4 of the fourth dry material may satisfy: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material may be ≥0.76g / cm 3 , which can make the coarser particles in the dry material have a larger bulk density, so that the final bulk density of the dry material is ≥1.32g / cm 3, thereby effectively reducing the internal porosity of the dry material to obtain a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode.
[0053] The particle size D1 of the first particle size dry material can satisfy the following: D1 = 0.005 mm, 0.010 mm, 0.015 mm, 0.020 mm, 0.025 mm, 0.030 mm, 0.035 mm, 0.040 mm, 0.045 mm, 0.050 mm, 0.055 mm, 0.060 mm, 0.065 mm, 0.070 mm and 0.074 mm.
[0054] The bulk density of the first particle size dry material can be 0.97 g / cm 3 , 0.98g / cm 3 , 0.99g / cm 3 or 1.00g / cm 3 .
[0055] The particle size D2 of the second particle size dry material may satisfy the following: D1 = 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm.
[0056] The bulk density of the second particle size dry material can be 0.90 g / cm 3 , 0.91g / cm 3 , 0.93g / cm 3 , 0.94g / cm 3 , 0.95g / cm 3 , 0.96g / cm 3 or 0.97g / cm 3 .
[0057] The particle size D3 of the third particle size dry material can satisfy: D3 = 1.1 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm or 4.0 mm.
[0058] The bulk density of the third granular dry material can be 0.82 g / cm 3 , 0.83g / cm 3 、0.84g / cm 3 , 0.85g / cm 3 , 0.86g / cm 3
[0059] The particle size D4 of the fourth particle size dry material may satisfy the following: D4=4.1 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm or 8.0 mm.
[0060] The bulk density of the fourth particle size dry material can be 0.76 g / cm 3 , 0.77g / cm 3 , 0.78g / cm 3 or 0.79g / cm 3 .
[0061] It should be noted that the first particle size dry material, the second particle size dry material, the third particle size dry material and the fourth particle size dry material refer to dry materials with different particle size distributions, and these dry materials with different particle sizes have different bulk densities.
[0062] It should be noted that the first particle size dry material is obtained by subsequent grinding and screening of the second particle size dry material, the third particle size dry material or the fourth particle size dry material.
[0063] In some optional embodiments, the total bulk density of the dry materials of multiple particle sizes is ≥1.32 g / cm 3 ;
[0064] In these embodiments, the total bulk density of the dry material of multiple particle sizes may be ≥ 1.32 g / cm 3 This shows that the dry material has a good bulk density, and the dry material with good bulk density has a higher compactness. The dry material with high compactness can reduce the grain resistance and interface resistance, thereby improving the conductivity of the prebaked carbon anode.
[0065] In some optional embodiments, the conductive carbon material includes at least one of the following:
[0066] Semi-graphite, artificial graphite, natural graphite and spent anode carbon blocks; and / or
[0067] The binder includes coal tar pitch;
[0068] In these embodiments, the conductive carbon material may include: at least one of semi-graphite, artificial graphite, natural graphite and residual anode carbon blocks, which can enable the conductive carbon material to have good conductive properties to effectively improve the conductive properties of the prebaked carbon anode. In addition, the binder may include coal tar, which can further improve the compactness of the dry material powder. The dry material with higher compactness can improve the density of the prebaked carbon anode to isolate the entry of external oxygen, thereby improving the antioxidant properties of the prebaked carbon anode.
[0069] In some optional embodiments, the ash content of the conductive carbon material is less than 0.5%, the specific resistance of the conductive carbon material is less than or equal to 180 μΩ·m, and the Lc value of the conductive carbon material is less than or equal to 0.5%.
[0070] In these embodiments, the ash content of the conductive carbon material may be <5%, the specific resistance of the conductive carbon material may be ≤180 μΩ·m, and the Lc value of the conductive carbon material may be The conductivity of the prebaked carbon anode can be improved by replacing part of the calcined petroleum coke with conductive carbon materials.
[0071] In some optional embodiments, the resistivity of the prebaked carbon anode is ≤46 μΩ·m, the volume density of the prebaked carbon anode is ≥1.58 g / cm3, and the air reactivity residual rate of the prebaked carbon anode is ≥80%;
[0072] In these embodiments, the resistivity of the prebaked carbon anode can be ≤46 μΩ·m, the volume density of the prebaked carbon anode can be ≥1.58 g / cm3, and the air reactivity residual rate of the prebaked carbon anode can be ≥80%, which indicates that the prebaked carbon anode has good electrical conductivity, high compactness and high oxidation resistance.
[0073] Figure 2 A schematic flow chart of a method for preparing a prebaked carbon anode provided in an embodiment of the present application is shown as an example;
[0074] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a method for preparing the prebaked carbon anode, the method comprising:
[0075] S1. calcining petroleum coke to obtain calcined petroleum coke;
[0076] S2. The conductive carbon material and the calcined petroleum coke are mixed to obtain a dry material;
[0077] S3. Wetting the dry material with a binder to obtain a mixed material;
[0078] S4. calcining the mixture to obtain a prebaked carbon anode.
[0079] This method is a method for preparing the above-mentioned prebaked carbon anode. The specific composition of the prebaked carbon anode can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0080] It should be noted that before mixing, the conductive carbon material and calcined petroleum coke can be graded according to different particle sizes using multi-stage crushing or grinding classification to facilitate the mutual complementation and interlocking of different particle size powder materials in the conductive carbon material and calcined petroleum coke in the subsequent mixing stage.
[0081] It should be noted that the mixing can be achieved by mechanical vibration, stirring or ultrasonic dispersion to promote the full mixing of the conductive carbon material and the calcined petroleum coke, so as to promote the mutual complementation and interlocking of the same particle size powders in the calcined petroleum coke and the conductive carbon material, so as to reduce the internal porosity of the dry material, thereby obtaining a dry material with high compactness. The dry material with high compactness can reduce the grain resistance and interface resistance, thereby improving the conductivity of the prebaked carbon anode.
[0082] In some optional embodiments, the wettability of the binder relative to the mixture is greater than 1.39, the wettability of the binder relative to the calcined petroleum coke in the mixture is greater than 1.36, and the wettability of the binder relative to the conductive carbon material in the mixture is greater than 1.56;
[0083] In these embodiments, the wettability of the binder relative to the mixture can be >1.39, and the wettability of the binder relative to the calcined petroleum coke in the mixture can be >1.36, and the wettability of the binder relative to the conductive carbon material in the mixture can be >1.56. The binder can be used to effectively improve the compactness of the calcined petroleum coke and the conductive carbon material in the dry material, thereby effectively improving the compactness of the mixture. The mixture with higher compactness can improve the density of the prebaked carbon anode to isolate the entry of external oxygen, thereby improving the antioxidant properties of the prebaked carbon anode.
[0084] In some optional embodiments, the roasting includes a preheating section and a roasting section, the heating rate of the preheating section is ≤10°C / min, and the roasting temperature of the roasting section is ≥1060°C;
[0085] In these methods, the roasting can include a preheating section, a heating section and a roasting section, and the heating rate of the preheating section can be ≤10°C / min. The preheating in the preheating section can be used to initially promote the bonding of the various materials in the mixture and promote the overflow of volatiles in the mixture. The roasting temperature of the roasting section can be ≥1060°C, which can promote the dry material and the binder in the mixture to be more tightly bonded after sintering treatment, thereby improving the density of the prebaked carbon anode.
[0086] The present application is further described below with reference to specific examples. Experimental methods in the following examples where specific conditions are not specified are generally measured in accordance with industry standards; if there are no corresponding industry standards, they are carried out in accordance with common international standards, conventional conditions, or conditions recommended by the manufacturer.
[0087] Example 1
[0088] like Figure 1As shown, a prebaked carbon anode with high conductivity and oxidation resistance, the raw materials of the prebaked carbon anode include dry materials of multiple particle sizes and a binder, and the weight m1 of the dry materials of multiple particle sizes and the weight m2 of the binder satisfy the relationship:
[0089] m1:m2=85:15;
[0090] The raw materials of the dry material include calcined petroleum coke of multiple particle sizes and conductive carbon materials of multiple particle sizes, and the calcined petroleum coke and the conductive carbon materials satisfy the following relationship: m3:m4=80:20, and m31:m41=m3:m4;
[0091] In the formula, m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m01 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size.
[0092] The plurality of dry materials of particle size include a first dry material of particle size, a second dry material of particle size, a third dry material of particle size, and a fourth dry material of particle size;
[0093] The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is ≥0.97g / cm 3 ;
[0094] The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.9g / cm 3 ;
[0095] The particle size D3 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.82g / cm 3 ;
[0096] The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.76g / cm 3 ;
[0097] The total bulk density of the dry materials of various particle sizes is 1.33 g / cm 3 .
[0098] The conductive carbon material is artificial graphite;
[0099] The binder is coal tar.
[0100] The ash content of the conductive carbon material is 0.45%, the specific resistance of the conductive carbon material is 120μΩ·m, and the Lc value of the conductive carbon material is
[0102] like Figure 2As shown, a method for preparing a prebaked carbon anode comprises:
[0103] S1. calcining petroleum coke to obtain calcined petroleum coke;
[0104] S2. The conductive carbon material and calcined petroleum coke are mixed to obtain a dry material;
[0105] S3. Wetting the dry material with a binder to obtain a mixed material;
[0106] S4. calcining the mixed material to obtain a prebaked carbon anode.
[0107] The wettability of the binder to the calcined petroleum coke in the mixture is greater than 1.36, the wettability of the binder to the conductive carbon material in the mixture is greater than 1.56, and the wettability of the binder to the mixture is 1.40.
[0108] The roasting process includes a preheating section and a carbon roasting section. The heating rate of the preheating section is 8°C / min, and the roasting temperature of the roasting section is 1060°C.
[0109] Example 2
[0110] Based on the content disclosed in Example 1, the following modifications are further made:
[0111] The calcined petroleum coke and the conductive carbon material satisfy the following relationship: m3:m4=82:18, and m31:m41=m3:m4;
[0112] In the formula, m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m31 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size.
[0113] The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is 0.97g / cm 3 ;
[0114] The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.92g / cm 3 ;
[0115] The particle size D3 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.84g / cm 3 ;
[0116] The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.78g / cm 3 .
[0117] The bulk density of dry material is 1.33 g / cm 3 .
[0118] The conductive carbon material is artificial graphite;
[0119] The ash content of the conductive carbon material is 0.46%, the specific resistance of the conductive carbon material is 150μΩ·m, and the Lc value of the conductive carbon material is
[0121] The wettability of the binder relative to the mixed material is 1.39.
[0122] The roasting process includes a preheating section and a carbon roasting section. The heating rate of the preheating section is 8°C / min, and the roasting temperature of the roasting section is 1070°C.
[0123] Example 3
[0124] Based on the content disclosed in Example 1, the following modifications are further made:
[0125] The calcined petroleum coke and the conductive carbon material satisfy the following relationship: m3:m4=85:15, and m31:m41=m3:m4;
[0126] Wherein, m3 represents the total weight of the calcined petroleum coke, m4 represents the total weight of the conductive carbon material, m31 represents the weight of the calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size.
[0127] The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is 0.95g / cm 3 ;
[0128] The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.92g / cm 3 ;
[0129] The particle size D3 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.83g / cm 3 ;
[0130] The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.77g / cm 3 .
[0131] The bulk density of dry material is 1.33 g / cm 3 .
[0132] The conductive carbon material is semi-graphite;
[0133] The ash content of the conductive carbon material is 0.38%, the specific resistance of the conductive carbon material is 180μΩ·m, and the Lc value of the conductive carbon material is
[0135] The wettability of the binder relative to the mixed material is 1.38.
[0136] The roasting process includes a preheating section and a carbon roasting section. The heating rate of the preheating section is 10°C / min, and the roasting temperature of the roasting section is 1060°C.
[0137] Comparative Example 1
[0138] Based on the content disclosed in Example 1, the following modifications are further made:
[0139] No conductive carbon material is added.
[0140] Related experiments and effect data:
[0141] The resistivity, electrical conductivity, bulk density and air reactivity residual rate of the prebaked carbon anode obtained in each embodiment and comparative example were statistically analyzed, and the results are shown in Table 1. The resistivity of the prebaked carbon anode was measured in accordance with the "Standard for Determination of Room Temperature Resistivity of Cathode Carbon Blocks and Prebaked Anodes" recorded in Part 2 of YS / T 63.2 "Test Methods for Carbon Materials for Aluminum"; the bulk density of the prebaked carbon anode was measured in accordance with the "Determination of Apparent Density - Dimensional Method Standard" recorded in Part 7 of YS / T 63.7 "Test Methods for Carbon Materials for Aluminum"; and the air reactivity residual rate of the prebaked carbon anode was measured in accordance with the "Determination of Air Reactivity - Mass Loss Method Standard" recorded in Part 11 of YS / T 63.11 "Test Methods for Carbon Materials for Aluminum".
[0142] Table 1 Resistivity, bulk density and air reactivity residual rate of prebaked carbon anodes of various embodiments and comparative examples
[0143]
[0144] As shown in Table 1, the prebaked carbon anode provided in the embodiment of the present application has high conductivity and oxidation resistance, and its resistivity is as low as 45.3 μΩ·m and its volume density is ≥1.58 g / cm 3 , the air reactivity residual rate is ≥80%, indicating that the prebaked carbon anode achieves the simultaneous improvement of electrical conductivity and antioxidant properties.
[0145] In summary, the embodiments of the present application provide a prebaked carbon anode with high conductivity and oxidation resistance. The conductivity of the prebaked carbon anode is improved by using conductive carbon material to replace part of the calcined petroleum coke. In addition, the calcined petroleum coke and the conductive carbon material have the same particle size powders that complement each other to reduce the internal porosity of the dry material, thereby obtaining a dry material with high compactness, thereby improving the conductivity of the prebaked carbon anode. In addition, the addition of a binder can further increase the compactness of the dry material powder to improve the density of the prebaked carbon anode, thereby improving the oxidation resistance of the prebaked carbon anode.
[0146] In addition, the embodiment of the present application provides a prebaked carbon anode with high conductivity and oxidation resistance, which achieves a simultaneous improvement in the conductivity and density of the prebaked carbon anode, thereby enabling the prebaked carbon anode to have extremely high conductivity and oxidation resistance, providing strong technical support for energy saving and consumption reduction in aluminum electrolysis.
[0147] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but rather is intended to conform to the broadest scope consistent with the principles and novel features claimed herein.
Claims
1. A prebaked carbon anode having high electrical conductivity and oxidation resistance, characterized in that: The raw materials of the prebaked carbon anode include dry materials of multiple particle sizes and a binder, and the total weight m1 of the dry materials of multiple particle sizes and the weight m2 of the binder satisfy the relationship: m1:m2=(82:18)-(88:12); The raw materials of the dry material include calcined petroleum coke of multiple particle sizes and conductive carbon materials of multiple particle sizes, and the calcined petroleum coke and the conductive carbon materials satisfy the following relationship: m3:m4=(80~95):(5~20), and m31:m41=m3:m4, In the formula, m3 represents the total weight of calcined petroleum coke, m4 represents the total weight of conductive carbon material, m31 represents the weight of calcined petroleum coke of the first particle size, and m41 represents the weight of the conductive carbon material of the second particle size; the first particle size is the same as the second particle size.
2. The prebaked carbon anode according to claim 1, characterized in that: The first particle size and the second particle size are respectively greater than 0 and less than or equal to 8 mm.
3. The prebaked carbon anode according to claim 1 or 2, characterized in that: The dry materials of multiple particle sizes include a first particle size dry material, a second particle size dry material, a third particle size dry material and a fourth particle size dry material; The particle size D1 of the first particle size dry material satisfies: 0<D1≤0.074mm, and the bulk density of the first particle size dry material is ≥0.97g / cm 3 ; The particle size D2 of the second particle size dry material satisfies: 0<D2≤1mm, and the bulk density of the second particle size dry material is ≥0.9g / cm 3 ; The particle size D2 of the third particle size dry material satisfies: 1mm<D3≤4mm, and the bulk density of the third particle size dry material is ≥0.82g / cm 3 ; The particle size D4 of the fourth particle size dry material satisfies: 4mm<D4≤8mm, and the bulk density of the fourth particle size dry material is ≥0.76g / cm 3 .
4. The prebaked carbon anode according to claim 1, characterized in that: The total bulk density of the dry material of multiple particle sizes is ≥1.32 g / cm 3 .
5. The prebaked carbon anode according to claim 1, characterized in that: The conductive carbon material comprises at least one of the following: Semi-graphite, artificial graphite, natural graphite and residual anode carbon blocks; and / or The binder includes coal tar pitch.
6. The prebaked carbon anode according to claim 1, characterized in that: The ash content of the conductive carbon material is less than 0.5%, the specific resistance of the conductive carbon material is less than or equal to 180 μΩ·m, and the Lc value of the conductive carbon material is less than or equal to 0.5%.
7. The prebaked carbon anode according to claim 1, characterized in that: The resistivity of the prebaked carbon anode is ≤46 μΩ·m, and the volume density of the prebaked carbon anode is ≥1.58 g / cm 3 , the air reactivity residual rate of the prebaked carbon anode is ≥80%.
8. A method for preparing the prebaked carbon anode according to any one of claims 1 to 7, characterized in that: The method comprises: calcining petroleum coke to obtain calcined petroleum coke; Mixing the conductive carbon material and the calcined petroleum coke to obtain a dry material; Using an adhesive to wet the dry material to obtain a mixed material; The mixed material is molded, and then the molded mixed material is calcined to obtain a prebaked carbon anode.
9. The method according to claim 8, characterized in that The wettability of the binder to the calcined petroleum coke in the mixture is greater than 1.36, the wettability of the binder to the conductive carbon material in the mixture is greater than 1.56, and the wettability of the binder to the mixture is greater than 1.
39.
10. The method according to claim 8, characterized in that The roasting comprises a preheating section and a roasting section, the heating rate of the preheating section is ≤10°C / min, and the roasting temperature of the roasting section is ≥1060°C.
Citation Information
Cited By
Heat-preservation anti-oxidation coating for anode carbon block and preparation method of heat-preservation anti-oxidation coating
CN119980360A
Pre-baked carbon anode having high electrical conductivity and oxidation resistance and preparation method therefor
WO2026076959A1